From now on: experiences from user-based research in remote settings - Correa, Claiton Marques; de Freitas, Gabriel Viegas Maciel; Eberhardt, André Luis dos Santos; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
The COVID-19 disease changed our society in many ways. The social distancing restrictions became mandatory as governments measure to limit the virus spread. These restrictions forced medical appointments, events, meetings, classes, and research experiments, to name a few, to move to an online format. In this new scenario, researchers were also required to redesign their studies, especially the user-based ones. While the virus is still a threat, researchers focus on understanding its long-term effects in research. From this perspective, we explored experiences from three case studies carried out last year: a focus group, a communicability evaluation, and an user observation study. We report on adaptations, challenges, opportunities, and lessons learned in conducting researches with human participation during the social restrictions. The main contribution of this work is a reflection on difficulties, advantages, and changes that may remain in a post-pandemic period from the experiences we met as Human-Computer Interaction researchers in conducting such remote studies. We conclude that the three methods analyzed could be successfully performed with small adjustments without compromising the user involvement in performing the tasks of each study.